The Aqueous Crude Extracts of and Reduce Immobility Faster Than Fluoxetine Through GABA Receptors in Rats Forced to Swim - Juan Francisco Rodríguez-Landa PhD; Jonathan Cueto-Escobedo PhD; Luis Ángel Flores-Aguilar MSc; Gilberto Uriel Rosas-Sánchez MSc; María de Jesús Rovirosa-Hernández PhD; Francisco García-Orduña MSc; Miguel Carro-Juárez PhD (SAGE Publishing, 2018)
Background. Montanoa frutescens and Montanoa grandiflora have been indistinctly used for centuries in traditional Mexican medicine for reproductive impairments, anxiety, and mood disorders. Preclinical studies support their aphrodisiac and anxiolytic properties, but their effects on mood are still unexplored. Methods. The effects of 25 and 50 mg/kg of M frutescens and M grandiflora extracts were evaluated on days 1, 7, 14, 21, and 28 of treatment, and compared with fluoxetine (1 mg/kg) and Remotiv (7.14 mg/kg) in Wistar rats. The participation of GABA A receptor in the effects produced by the treatments was explored. Results. Montanoa extracts reduced immobility since day 1 of treatment, while fluoxetine and Remotiv required 14 days. The GABA A antagonism blocked the effects of Montanoa extracts, but not of fluoxetine or Remotiv. Conclusions. Montanoa extracts prevented quickly the stress-induced behaviors in the swimming test through action at the GABA A receptor, exerting a protective effect different to the typical antidepressants drugs.